2006
DOI: 10.2166/wst.2006.592
|View full text |Cite
|
Sign up to set email alerts
|

The effect of climate change on urban drainage: an evaluation based on regional climate model simulations

Abstract: That we are in a period of extraordinary rates of climate change is today evident. These climate changes are likely to impact local weather conditions with direct impacts on precipitation patterns and urban drainage. In recent years several studies have focused on revealing the nature, extent and consequences of climate change on urban drainage and urban runoff pollution issues. This study uses predictions from a regional climate model to look at the effects of climate change on extreme precipitation events. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…For example, under a doubled CO 2 climate-change scenario the 1 in 100-year flood becomes a 1 in 10-year event for Canberra, Australia (Schreider et al, 2000). However, detailed hydrological modelling for urban areas continues to be confounded by a lack of high-resolution (space and time) climate-change scenarios (Grum et al, 2006;Wilby, 2007). Indeed, many climate models treat built areas as vegetated surfaces, whilst realistic simulations of localised, highintensity, summer precipitation events have yet to be realised (see Fowler & Ekström, 2009).…”
Section: Urban Areasmentioning
confidence: 99%
“…For example, under a doubled CO 2 climate-change scenario the 1 in 100-year flood becomes a 1 in 10-year event for Canberra, Australia (Schreider et al, 2000). However, detailed hydrological modelling for urban areas continues to be confounded by a lack of high-resolution (space and time) climate-change scenarios (Grum et al, 2006;Wilby, 2007). Indeed, many climate models treat built areas as vegetated surfaces, whilst realistic simulations of localised, highintensity, summer precipitation events have yet to be realised (see Fowler & Ekström, 2009).…”
Section: Urban Areasmentioning
confidence: 99%
“…Previous studies on climate change, Mailhot and Duchesne [20], Wernstedt and Carlet [22], Mailhot et al [30], Grum et al [35], He et al [36], and Brown [37] have suggested the replacement of the current design standard by a simple and robust method that includes the effects of climate change. However, these studies are limited for the following reasons.…”
Section: Introductionmentioning
confidence: 99%
“…The time-scales at which these events are described at are important, to assess whether the projections are relevant. Grum, Jorgensen, Johansen and Linde (2006) [28] concluded in their study of the impact of climate change on urban drainage that extreme precipitation events affecting urban drainage and causing flooding would become more frequent, therefore requiring changes in the design methodology for drainage systems.…”
Section: Climate Change and Extreme Precipitation Eventsmentioning
confidence: 99%